Work-sharing for a sustainable economy - Klara Zwickl; Franziska Disslbacher; Sigrid Stagl (WWWforEurope, 2016)
Achieving low unemployment in an environment of weak growth is a major policy challenge; a more egalitarian distribution of hours worked could be the key to solving it. Whether worksharing actually increases employment, however, has been debated controversially. In this article we present stylized facts on the distribution of hours worked and discuss the role of work-sharing for a sustainable economy. Building on recent developments in labor market theory we review the determinants of working long hours and its effect on well-being. Finally, we survey work-sharing reforms in the past. While there seems to be a consensus that worksharing in the Great Depression in the U.S. and in the Great Recession in Europe was successful in reducing employment losses, perceptions of the work-sharing reforms implemented between the 1980s and early 2000s are more ambivalent. However, even the most critical evaluations of these reforms provide no credible evidence of negative employment effects; instead, the overall success of the policy seems to depend on the economic and institutional setting, as well as the specific details of its implementation.
Keywords: D1; D3; E24; J08; J2; 330; Work-sharing; Working hours; Labor Supply; Labor Demand; Environmental Sustainability